The Influence of Discovery Learning on Mathematics Learning Motivation in Elementary Schools - Oktaria, Sesmita; Ain, Siti Quratul (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the effect of the Discovery Learning approach on students’ motivation in learning mathematics. The research employed a quantitative pre-experimental method with a one-group pretest–posttest design. The subjects were 30 third-grade students selected through purposive sampling. The instrument used was a motivation questionnaire, consisting of 15 items tested for validity and reliability, all of which met the required standards (Cronbach’s Alpha = 0.853). Data analysis included normality, linearity, and paired sample t-tests. The findings show that students’ average motivation score increased by 20.433 points, with a significance value of 0.000 (p < 0.05). These results indicate that Discovery Learning has a significant and positive effect on students’ mathematics learning motivation.